2019
DOI: 10.1108/jta-02-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the efficiency of medical tourism industry in EU member states

Abstract: Purpose -Under the Directive 2011/24/EU, medical tourism and cross-border health are interrelated terms regarding the freedom to move to get the most accessible medical treatment into EU Member State within the defined procedures for reimbursement. Little known empirically regarding the efficiency of the cross-border health/medical tourism industry. This study aims to measure its efficiency in Europe for the years 2010-2014, by using Data Envelopment Analysis (DEA).Design/methodology/approach -Data obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
0
7
0
4
Order By: Relevance
“…Furthermore, the EU directive guarantees the right to a copy of your medical records and, if you need follow-up assistance, you are entitled to receive the same follow-up care that would have been provided in your home country. According to Androutsou and Metaxas [35], there has not been a considerable efficiency improvement after the implementation of the EU directive, because the Directive was not properly disseminated to European citizens. However, these authors point out that cross border health/medical tourism is gaining great interest, and an early-stage collection of reliable data has been performed by member states.…”
Section: Discussion: Opportunities and Challenges In The Futurementioning
confidence: 99%
“…Furthermore, the EU directive guarantees the right to a copy of your medical records and, if you need follow-up assistance, you are entitled to receive the same follow-up care that would have been provided in your home country. According to Androutsou and Metaxas [35], there has not been a considerable efficiency improvement after the implementation of the EU directive, because the Directive was not properly disseminated to European citizens. However, these authors point out that cross border health/medical tourism is gaining great interest, and an early-stage collection of reliable data has been performed by member states.…”
Section: Discussion: Opportunities and Challenges In The Futurementioning
confidence: 99%
“…Lubowiecki-Vikuk and Dryglas (2019b) Decreasing public health funding in developing countries that experiment with tourism-related patterns of healthcare system commercialization de Castro et al 2015Governments would have to ensure that tax revenues generated from healthcare tourism are reinvested in healthcare development initiatives Then residents are likely to notice concrete benefits from this sector Yim (2005) Sustainable medical tourism is important because companies and regions that create significant value have a positive economic impact on the development of the tourism sector and the surrounding area Perkumien_ e et al (2019) SocietyAccess to a local community living close to medical tourism services for healthcare Bristow et al (2011) Facilitators' cooperation perspectives in sustainable medical tourism should be highly beneficial for participants and medical tourists Inelmen et al (2015), Perkumien_ e et al 2019, Jackson and Barber (2015) Healthcare tourism has the potential of transferring healthcare problems associated with the developed world to the developing world Vijaya 2010Healthcare systems in EU countries may be more effective for medical tourists than for residents Androutsou and Metaxas (2019) Good quality of treatment, trademarks, famous doctors, and intellectual property as a driver for sustainability in medical tourism Bolos (2013) Environment Ways to properly remove and dispose of medical waste that "threatens local water supplies and the public health of nearby residents"…”
Section: Discussionmentioning
confidence: 99%
“…Leleu et al adopted the DEA approach to investigate the efficiency of private hospitals in the United States and the factors that affect it and found that hospitals located in more competitive markets were more efficient than those located in less competitive markets [ 8 ]. Some European researchers have performed DEA to measure the efficiency of public healthcare systems and the healthcare industry in general [ 9 , 10 ]. Jiang et al employed the DEA model to evaluate hospitals' efficiency and effectiveness before and after healthcare reforms were implemented in China, and found that reform did not improve the efficiency of hospital operations in Chia to any great extent [ 11 ].…”
Section: Introductionmentioning
confidence: 99%